A review of energy consumption and saving in extra-long tunnel operation ventilation in China. (January 2016) - Guo, Chun; Wang, Mingnian; Yang, Lu; Sun, Zhitao; Zhang, Yunlong; Xu, Jianfeng
Abstract: Green and renewable, wind is one of the major ways to produce power. However, natural wind used for tunnel ventilation is often neglected. Natural wind is usually regarded as resistance. Every year, unchanging ventilation mode and unreasonable control strategy lead to huge energy consumption and economic loss In China. This paper mainly discusses and analyzes the current situation of energy consumption in extra-long tunnel operation ventilation in China. It proposes the natural wind utilization in extra-long segmented tunnels. Therefore, a scientific and theoretical calculation method for extra-long tunnels located in climate separation zone is presented in this paper. Principles of natural wind in each tunnel section are obtained based on long-term monitored meteorological factors. A feasible optimized energy-saving ventilation strategy is put forward, which utilizes natural wind and will minimize the operation energy consumption. It is concluded that, the results about operation energy consumption from this paper can provide useful technical supports in design, operation and management for tunnels all over the world.